Impact of Cash Flow Components, Net Profit, on Stock Returns - Imas Masjitoh Ramdani; Anak Agung Gde Satia Utama (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to obtain empirical evidence regarding the effect of Cash Flow Components, Net Income, and the level of Stock Returns. This study is a quantitative study using secondary data obtained from the annual financial reports of transportation industry companies on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The population in this study is Transportation Industry Companies listed on the IDX. The company sample was determined using a purposive sampling technique. The analysis method used is multiple regression analysis. The results of the study indicate that cash flow components do not have a significant effect on stock returns, net income has a significant effect on stock returns, and does not have a significant effect on stock returns.